Diagnostic Abilities of Novice Teachers - Tołoczko, Ewa (Theory and Practice of Second Language Acquisition, 2023)
This paper discusses diagnostic abilities of novice teachers of English as a foreign language in Poland as demonstrated through analyzing critical incidents (CIs). A case study, designed to explore patterns and regularities in cognitive processes that practitioners activate to examine disorienting situations in their educational context, provided evidence of effective mental work of beginner teachers at the verbal and conceptual levels. Specifically-structured written reports on what the instructors considered critical moments in their teaching practice served as a tool to verbalize how they represent, interpret, and value phenomena in the FL classroom by activating and integrating various sources of professional knowledge. The data analysis, which included both identification of the character of mental representations the subjects stimulated during the recall as well as higher order thinking operations on these representations, led to the conclusion that the inexperienced teachers show a degree of efficacy to register relations and variation in classroom realities, to problematize the unproblematic, to take position on matters, and to formulate relevant feedback for their future didactic moves. This encourages a hypothesis that teachers’ diagnostic abilities are not necessarily determined by the current state of their professional expertise and that limited classroom experience does not suppress adequate cognitive and affective responses to problems in beginner practitioners.